Optimization of Area of CMOS Differential Amplifier Using Modified PSO Algorithm - Ratan S.; Mondal D.; Kumar C.; Kumar A.; Jarwal D.K.; Mishra A.K.; Kar R.; Jit S. (My University, 2025)
As the complexity of the modern era electronic circuits increased; there arose a need for more accurate devices. The use of high-end modern equipment has penetrated into different levels of society that the need for more compact and less costly devices became the key objective of circuit designing. Keeping these two points in mind, the designing., as well as optimization., is carried out to find the best possible design parameter values. This work presents the optimized values of various parameters of a CMOS differential amplifier for better performance. The modified particle swarm optimization (MPSO) technique is chosen for optimizing the circuit area. The obtained results from MPSO is also verified in the Cadence. © 2018 IEEE.